Training, support and management of sessional teaching staff : final report. - Chalmers, Denise; Herbert, Debra; Hannam, Rachel; Smeal, Georgia; Whelan, Karen (Australian Universities Teaching Committee, 2003)
The project's initial activities included a thorough review of the literature, and a limited survey that was conducted across the sector of sessional teachers and their supervisors. A key finding was that the availability of sessional teachers offers significant benefits to universities in terms of flexibility, diversity and financial savings, however there is little in the way of formal, systematic, or centralised policies or approaches to their support, training or management at the university or organisational unit level. The project's overall findings include the need to allow for organisational unit responses to issues of training, managing and supporting sessional staff within a wider university framework. That is, responsibility for these tasks needs to be delegated to the most appropriate level, but to be situated in a general structure of clear policies, processes and practices. Resources need to be allocated to ensure that sessional teaching staff are appropriately managed, supported and trained. [p.i, ed]